"Coke on Tick": exploring the cocaine market in the UK through the lens of financial management. Issue 2 (2nd May 2017) - Hall, Alexandra; Antonopoulos, Georgios A.
Abstract : Purpose: This paper aims to offer detailed preliminary data and analysis that focuses specifically on the structures and financial aspects of the UK cocaine market. Design/methodology/approach: This paper is based on in-depth interviews with – among others – four active criminal entrepreneurs involved in powder cocaine supply in the UK. Furthermore, along with a review of relevant literature and open sources, in-depth interviews were undertaken with a range of experts with knowledge of the cocaine market. These experts include law enforcement agents and independent academics/researchers who have researched the cocaine market in the UK and internationally. Findings: The cocaine market is a fragmented business dependent on networks of individual entrepreneurs and groups. At the core of collaborations often lie family, ethnic or kinship relationships and relationships forged within legal businesses and in prison. Capital investment practices in this market are flexible, "messy" and mutating, and money comes from a range of different sources. Credit is an integral feature of the cocaine business in the UK. The financial management of the cocaine trade is a result of (and reflects) a number of factors, such as the fragmented and decentralised nature of the trade. Originality/value: Empirical research into financial aspects of organised crime manifestations is important for the assumptions that are part of public debate to be tested. In addition, understanding the broader range of financial aspects of organised crime is an important component of the process of crimes for gain and can contribute to both better investigation and better prevention.